Interaction between Human Serum Albumin and Different Anatase TiO2 Nanoparticles: A Nano-bio Interface Study - Viviana Vergaro; Claudia Carlucci; Mariafrancesca Cascione; Caterina Lorusso; Francesca Conciauro; Barbara Federica Scremin; Paolo Maria Congedo; Giuseppe Cannazza; Cinzia Citti; Giuseppe Ciccarella (Nanomaterials and Nanotechnology, 2015)
In this investigation, differently shaped and surface functionalized TiO2 anatase nanoparticles and human serum albumin (HSA) were selected to study protein- nanoparticles interaction both in a solution and on flat surfaces, thereby mimicking a medical device. Anatase nanocrystals were characterized by transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) surface analysis and dynamic light scattering (DLS). The protein- nanoparticles’ interactions and their eventual reversibility were studied by pH dependent ζ- potential measurements in different media: ultra-pure water, a phosphate buffer simulating physiological conditions and in a culture medium supplemented with foetal bovine serum. The protein corona masking effect was evidenced and the interaction HSA-nanocrystals resulted irreversible. The interaction HSA-silicon supported TiO2 nanocrystals films was studied by atomic force microscopy (AFM), and resulted driven by the substrate hydrophilicity degree plus was different for the diverse range of nanocrystals tested. Surface roughness measurements showed that on some of the nanocrystals, HSA were arranged in a more globular manner. A lower protein affinity was found for nanocrys‐ tals that had a smaller primary particle size, which may correspond to their higher biocompatibility. This nano-bio interface research aimed to study the HSA protein-TiO2 anatase nanocrystals under conditions similar to those for in vitro and in vivo toxicity analyses.